Analisis Kewirausahaan Pelaku Usaha Kecil Pengrajin Tempe Desa Sumberagung, Kecamatan Moyudan, Kabupaten Sleman - Kristiana Sri Utami (HOME, 2019)
Efforts to develop MSMEs are currently the focus of the government. The ability of these business units is strongly influenced by entrepreneurial aspects. The ability of innovation and courage to face risks play a role in the development of MSMEs. Therefore, for small industries to develop, the development of entrepreneurial aspects for MSMEs is a very important factor to consider. Research on these tempe artisans units uses descriptive analysis by integrating qualitative and quantitative approaches. The variables of entrepreneurship consist of vision, planning, and courage to face risk. Data collection is conducted using structured interviews, documentation, and questionnaires. The results of the analysis provide clues to various efforts that need to be carried out to develop entrepreneurship for tempe artisans. This study concludes that tempe artisans are still very weak in the aspects of planning, namely marketing, production, HR and financial planning. While the aspects of vision and courage to take risks are good enough. The role of other parties, both government and private, is needed in the planning aspect. to assist the development of these business units. The role of this party is in the form of easiness in capital, training in planning and management and assistance, so that the tempe business unit as part of the creative industry in Sleman Regency can develop well.